Political Exegesis of the Holy Quran: A Rational and Critical vision - Zakir Aras; Sohirin Mohammad Solihin (Al-Jami'ah: Journal of Islamic Studies, 2022)
This study deals with the exposition of political orientation in giving exegetical understanding of the Holy Qur’an with the use of rational and critical vision. It also attempts to analyse the books on sciences of the Quran to reveal the advantegous and disadvantageous for those who subcribe what so-called ‘the modern way of exegesis’. In addition, it presents the efforts of previous exegetical notion as well as the contribution of contemporary scholars in dealing with the issue of political exegesis by explaining their political direction. Moreover, it aims at giving scientific solutions and presenting rational responses with regard to the lacking aspects of the methodology within political exegesis of the book of Allah and to disclose the thing which comes closer to the truth. The study relied on the descriptive and analytical approach, where to discuss in the folds of the research and analytical based on exploring political interpretation and monitoring its pros and cons. There is no doubt that the Qur’an is the first source of Islamic legislation, and therefore it encompassed all social fields, and based on this basis, limiting the understanding and interpretation of the Qur’an to a specific thing or to a specific era or a method of curriculum is something that contradicts the Qur’an itself. Just as we welcome the various explanatory methods and their methods and colors, we must welcome the political interpretation of our days as long as it adopts the right approach and the good methods. However, it is not possible to deal with the entire Qur’an with a naive political perspective, and to interpret the Book of God according to political requirements and concepts, as it will lead to the emergence of political movements or military groups that give great interest in the political aspect of the Qur’an, so the Holy Qur’an enters into a political battle that the message of the Holy Qur’an does not aim at.Artikel ini membahas orientasi politis dalam penulisan tafsir Qur’an dengan pendekatan yang lebih rasional dan kritis. Artikel ini juga menganalisis literatur kajian tentang Qur’an serta menunjukkan keuntungan dan kerugian dari istilah yang dikenal sebagai pendekatan modern dalam tafsir Qur’an. Selain itu juga menjelaskan kajian–kajian tafsir sebelumnya hingga kontribusi kajian sarjana tafsir saat ini yang terkait dengan pembahasan politisasi tafsir berserta kecenderungan politisnya. Disamping itu, artikel ini memberikan solusi dan respon rasional berdasar pada aspek kesenjangan metodologi politisasi tafsir dan usaha mengungkapkan pada kebenaran. Kajian ini menggunakan pendekatan deskriptif dan analitik, dimana akan didasarkan pada eksplorasi berbagai penafsiran politis dan mengamati pendukung dan penentangnya. Tidak ada keraguan bahwa Qur’an adalah sumber hukum Islam yang pertama dan merangkum semua bidang, sehingga atas dasar ini membatasi pemahaman dan penafsiran Qur’an kepada sesuatu atau era tertentu atau kurikulum tertentu adalah sesuatu yang bertentangan dengan Qur’an itu sendiri. Seperti halnya kita menerima penjelasan tentang metode dan ragam yang sudah ada, maka kita juga harus menyambut baik ragam tafsir dan orientasinya saat ini selama menggunakan pendekatan yang tepat dan metode yang baik. Meski demikian, tidak mungkin berurusan dengan Qur’an yang perspektif tafsirannya naif dan mengikuti kecenderungan politik tertentu hingga memunculkan gerakan atau kelompok politik tertentu. Alih-alih justru membawa Qur’an dalam pertikaian politik dan jauh dari pesan-pesan Qur’an yang sebenarnya.